The Elements of Secularization in The Universal Declaration of Human Rights - Muhammad Ivan Hidayat; Mohammad Djaya Aji Bima Sakti; Nazlan Hafidz; Yusuf Al Manaanu (Tasfiyah: Jurnal Pemikiran Islam, 2022)
Abstract: Human Rights is a concept proposed by the West for supporting the justice and the welfare of human life, both in the realm of security, health, etc. In this case, the Western’s experience after two great wars has made them focus a lot on the formulation of human rights. This is evident from several declarations on human rights that were initiated by countries in Europe, one of which is the Universal Declaration of Human Rights (UDHR). However, within the UDHR, there are many doctrines that originate from the Western’s worldview, such as Secularization, Liberalization, etc. If it is examined this path, it is inseparable from one of the world's great dark organizations called Freemasonary, which gave the doctrinal stigma in the formulation of the UDHR. As a political movement that provides breakthroughs in new ideas, Freemasonry is a thought or philosophical  movement that deserves to be studied, because of its closed attitude but has a fundamental influence on several facts that occur, one of which is the Universal Declaration of Human Rights itself. In this paper the author will examine the history of the human rights declaration, starting from the influential figures in it to the content of the declaration which is full of typical Western doctrines above. Then the author will include an Islamic view that clearly has a different worldview of the concept in western human rights itself.